Compos(t)ing Loss: Transformation in the Telling - Laura Milner (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
Using composting as a metaphor, this author examines the transformative potential in writing about and bearing witness to stories of loss, particularly the death of a parent.